GAGASAN KEWENANGAN MAHKAMAH KONSTITUSI DALAM MENYELESAIKAN PERKARA CONSTITUTIONAL COMPLAINT BERDASARKAN UNDANG-UNDANG DASAR 1945 - Indah Permata Sari; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The Constitution of the Republic Indonesia 1945 and law of No. 8 of 2011 about Constitutional court haven’t constitutional complaint as constitutional court’s authority.that’s because be important to think again will add constitutional court’s authority to complete about constitutional complaint that violation of constitutional right that there is no path of its legal settlement can be handled by the constitutional court. The kind of research can be classified normative law research. The idea of the authority of the constitutional court in resolving constitutional complaint’s matter through constitutional court is to revise the constitution in 1945 order to broaden the interpretation of the authority possessed by the constitutional court.Keyword: Authority – Constitutional court – Constitutional complaint